Analysis of the Spatiotemporal Evolution of the Maurienne Swarm (French Alps) Based on Earthquake Clustering. Issue 7 (25th July 2022) - Minetto, Riccardo; Helmstetter, Agnès; Schwartz, Stéphane; Langlais, Mickaël; Nomade, Jérôme; Guéguen, Philippe
Abstract: Between August 2017 and March 2019, an intense seismic swarm was recorded in the Maurienne valley in the north of the Belledonne massif (Western French Alps). In order to study the spatiotemporal evolution of the Maurienne swarm, we created a high‐resolution catalog based on template matching, double‐difference relocation, and moment magnitudes. The catalog includes 71, 064 events with a maximum moment magnitude of 3.5 and a magnitude of completeness of 0.7. The seismic activity is interpreted as the reactivation of an N80 strike‐slip fault system called Fond de France. Moreover, earthquake relocation reveals the presence of a shallower fault system with the same strike, but opposite dip direction and smaller size. The presence of two distinct fault systems may explain the observed variation of the b ‐value with depth. The seismicity migrated asymmetrically in all directions during the course of about 15 months. Shorter migrations lasting 2–3 days are also observed. The different migration patterns suggest that the swarm is driven by several mechanisms, possibly pore‐pressure diffusion, aseismic slip, and earthquake interactions. Key Points: We use template matching, double‐difference relocations, and moment magnitudes to create a high‐resolution catalog of the Maurienne swarm At least two conjugate fault systems with opposite dip directions were reactivated during the swarm The complex migration of seismicity suggests that the swarm may be driven both by pore‐pressure diffusion and by earthquake interactions